School-Based Management in southeast Asia (MBS-SA): Demands or Education Needs? (Educational Management Studies in Thailand and Indonesia) - Deny Setiawan (Akademika: Jurnal Manajemen Pendidikan Islam, 2021)
This article discusses conceptual School-Based Management (SBM) which includes the contribution and implementation of the education process in managing the structure and organizing autonomous education (decentralized from the government to school). This article is made by reviewing and collecting information from various references both books, articles, and journals that are used as material in studying and conceptually adding insight to SBM. The idea of holding SBM is a good step to support the improvement and acceleration of the improvement of the quality of human resources in the field of education that is in accordance with the field conditions to solve problems more quickly and effectively, but it is also very risky for failure because all responsibilities and implementation are left to executor, where each region has different human resources (HR) and funding capabilities.